Students' Interest In Making Table Cloths Learning Using Fantasy Embroidery - Ernawati Ernawati (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2022)
This study started from the problem that students' interest in the competence of making tablecloths using fantasy embroidery was still lacking. The purpose of this study was to express students' interest in learning about the competence to learn the skills of making tablecloths using fantasy embroidery at MTsN Payakumbuh, Payakumbuh City. The method used in this research is the descriptive method. The population in this study was class VIII students, amounting to 198 students. The sample in this study is part of the population obtained by 40 students. The indicators in this study are the strength of students' motives, attention, and feelings of pleasure towards arts and culture subjects in learning the skills of making tablecloths using fantasy embroidery. This research instrument is in the form of a questionnaire, and the data analysis technique uses percentages. The results showed that the interest of class VIII students in arts and culture subjects in learning the skills of making tablecloths using fantasy embroidery at MTsN Payakumbuh was in the high category with an average score of 3.6 with an achievement rate of 72.5% of respondents. Student interest from the aspect of motive power obtained an average score of 3.36 with a respondent's level of achievement of 67.14%, including the high category, and student interest from the aspect of attention with obtained an average score of 3.72 with a respondent's achievement level of 74.5% including the high category and student interest in terms of feeling happy with obtained an average score of 3. 8 with an achievement level of 75.9% respondents included in the high category. It is recommended that students increase their interest in learning, and the teacher directs students more to growing students' interest in learning.